„Miejsce cieniem kryte” w domu nr 4 z Kościelisk, pow. Olesno, woj. Opolskie (próba rekonstrukcji) - problem budownictwa podcieniowego w kulturze przeworskiej - Michałowski, Andrzej (Folia Praehistorica Posnaniensia, 2018)
The article brings about another attempt to reconstruct the shape of house No. 4 from Kościeliska, Olesno district (Hedwigstein, Kr. Rosenberg) within the context of arcaded houses noticed at the Przeworsk culture settlements. The undertaken analysis makes possible a reinterpretation of the already published materials and proposes a new research strategy that addresses this issue more efficiently. This makes it possible to prove the existence of comer arcades in the architecture of the Przeworsk culture.